EFL College Students’ Perception in Using Hello English Application as An Autonomous Learning Activity to Increase Vocabulary - Ramadhana, Nur Alfath; Marlina, Leni (Journal of English Language Teaching, 2024)
The study aims to investigate the effectiveness of using the Hello English application as an autonomous learning activity to increase vocabulary EFL College students. The study’s importance is predicted to have both academic and practical implications. The research design was descriptive quantitative. The instrumentation of this research were questionnaire and interview. The technique of data collection was that the students were given questionnaires to find out about the effectiveness of using those applications as autonomous learning. The respondents will be able to give responses to each statement by clicking one of the responses (Strongly Disagree, Disagree, Agree, Strongly Agree) given. The data results on students’ perceptions, specifically concerning the physical aspect and psychological aspect of using the Hello English program are presented in the table.